A case of extremely prolonged viral shedding: Could cell cultures be a diagnostic tool to drive COVID-19 patient discharge?. (March 2021) - Mileto, Davide; Foschi, Antonella; Mancon, Alessandro; Merli, Stefania; Staurenghi, Federica; Pezzati, Laura; Rizzo, Alberto; Conti, Federico; Romeri, Francesca; Bernacchia, Dario; Meroni, Rachele; Rizzardini, Giuliano; et al.
Highlights: Case presentation of a patient positive for SARS-CoV-2 after 71 days from symptom onset. After acute infection, patients positive for SARS-CoV-2 may not be a source of COVID-19 infection. Viral culture can help interpreting SARS-CoV-2 positivity, limiting unnecessary isolation. Abstract: This study addressed the case of a patient with prolonged COVID-19 viral shedding, reported by Real-Time PCR, until 71 days from symptom onset. However, viral culture received negative results after 30 days from symptom onset. Therefore, viral culture may be a worthwhile test for patients requiring discharge, in particular for those presenting prolonged viral shedding.